Streptomyces sp. Sebagai Biofungisida Patogen Fusarium oxysporum (Schlecht.) f.sp. lycopersici (Sacc.) Snyd. et Hans. Penyebab Penyakit Layu Pada Tanaman Tomat (Solanum lycopersicum L.) - NURI MANDAN SARI; RETNO KAWURI; KHAMDAN KHALIMI (Agrotrop : Journal on Agriculture Science, 2012)
A research was conducted to isolate Streptomyces sp. of soil Udayana University campus in theBukit-Jimbaran, to obtain the most effective Streptomyces sp. which is effective in inhibit the growth ofFusarium oxysporum f.sp. lycopersici, and to test response of tomato plants with Streptomyces sp.culture against Fusarium wilt desease. Implementation phases of the research consisted of isolation andidentification of Streptomyces sp, test the inhibition against F. oxysporum f.sp. lycopersici, and in vivotest used by dyeing the roots of the tomato plant (Solanum lycopersicum) with Fusarium spores andafter 30 seconds the roots were dyeing Streptomyces culture. Furthermore, sterile soil in polybagwatered by Fusarium spores and Streptomyces culture at the same time. Based on morphologicalcharacteristic it found five isolates of Streptomyces sp.. The antagonist test showed Streptomyces sp.1 had ability (75%) against Fusarium, Streptomyces sp 2 (68,3%), Streptomyces sp. 3 (71,6%),Streptomyces sp. 4 (63,3%), and Streptomyces sp. 5 (21,6%). All Streptomyces suppressed thegrowth of Fusarium on tomato plants in glass house (p<0,05). Streptomyces sp.3 suppressed Fusariumwilt disease in tomato from 88% in control to 20%.